Enhanced recruitment of glutamate receptors underlies excitotoxicity of mitral cells in acute hyperammonemia - Li, Mingxian; Liu, Zhenqi; Lai, Ke; Liu, Hanwei; Gong, Lina; Shi, Haosong; Zhang, Weitian; Wang, Hui; Shi, Haibo (Frontiers in Cellular Neuroscience, 2022)
Hepatic encephalopathy (HE)—a major complication of liver disease—has been found to increase the risk of olfactory dysfunction, which may be attributed to elevated levels of ammonia/ammonium in the blood and cerebrospinal fluid. However, the cellular mechanisms underlying hyperammonemia-induced olfactory dysfunction remain unclear. By performing patch-clamp recordings of mitral cells (MCs) in the mouse olfactory bulb (OB), we found that 3 mM ammonium (NH4+) increased the spontaneous firing frequency and attenuated the amplitude, but synaptic blockers could prevent the changes, suggesting the important role of glutamate receptors in NH4+-induced hyperexcitability of MCs. We also found NH4+ reduced the currents of voltage-gated K+ channel (Kv), which may lead to the attenuation of spontaneous firing amplitude by NH4+. Further studies demonstrated NH4+ enhanced the amplitude and integral area of long-lasting spontaneous excitatory postsynaptic currents (sEPSCs) in acute OB slices. This enhancement of excitatory neurotransmission in MCs occurred independently of presynaptic glutamate release and re-uptake, and was prevented by the exocytosis inhibitor TAT-NSF700. In addition, an NH4+-induced increasement in expression of NR1 and GluR1 was detected on cytoplasmic membrane, indicating that increased trafficking of glutamate receptors on membrane surface in MCs is the core mechanism. Moreover, NH4+-induced enhanced activity of glutamate receptors in acute OB slices caused cell death, which was prevented by antagonizing glutamate receptors or chelating intracellular calcium levels. Our study demonstrates that the enhancement of the activity and recruitment of glutamate receptor directly induces neuronal excitotoxity, and contributes to the vulnerability of OB to acute hyperammonemia, thus providing a potential pathological mechanism of olfactory defects in patients with hyperammonemia and HE.